Anthropogenic Hazards and Their Impact Upon the Historical Cultural Landscape in Roșia Montană Area - NICULA, Gabriel; GAVRA, Camelia-Ina; VASILIȚĂ-CRĂCIUN, Ileana-Cristina (Studia Universitatis Babeș-Bolyai Geographia, 2023)
The cultural landscape is a result of the continuous human actions of satisfying the communities’ various needs and the response of the natural system, in its attempt to balance its components in relation to the modelling factor - the human society. Thus, the cultural landscape displays the imprint of the infinite possibilities of the human and natural joint manifestation, sometimes hazards bringing their own contribution to the shaping of the cultural landscape. Hazards, whether natural or anthropogenic, are unforeseen phenomena in terms of space or time of their manifestation, and most often have considerable negative consequences. In particular, anthropogenic hazards, which are directly or indirectly related to human activities, appear mainly as a manifestation of the resilience of natural elements in the cultural landscape, as a complex system. Thus, major interventions, such as mining in Roșia Montană area (an activity that had been lasting for over 2000 years) in relation to the unpredictable evolution of the social, economic, technological and political context (on local, national and global level) have favoured the manifestation of some unforeseen events with a negative connotation such as: complex pollution, depreciation of the living standards (in Roșia Montană area mostly due to the cessation of mining activities), demographic aging, etc. The complex analysis of these implications in the above mentioned area allows us to outline an eloquent assessment of the present state of the local cultural landscape and to identify the opportunities of systemic resilience. These include: the awareness of the planning, protection and conservation of the local historical cultural landscape as a primary need, restoration of the cultural landscape (through the aesthetic rehabilitation of degraded cultural elements), the implementation of projects that target the sustainable development of Roșia Montană, as a source of identity and sustainable development, the tourism conversion of activities, etc.